(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2024)
This paper is a narrative outcome of our fieldwork experiences with two Adivasi communities (Scheduled Tribes) on the outskirts of Mumbai City in India. Diverse, complex problems like urbanisation, capitalism, and climate change impact the livelihoods of these communities. The wicked nature of these problems perpetuates their social vulnerabilities, agro-biodiversity losses, and livelihood insecurities as they are constantly alienated, dispossessed, and displaced from their local environment and everyday forms of being. Given these circumstances, more than traditional community development approaches may be required locally. Engaging with these communities also implies that we engage with ecologies of knowing-in-being and repair, which, from a posthumanist perspective, guides us to the situated understanding of nature-culture entanglements, their relationalities, and the multiplicities of human-nonhuman associations.